2009
DOI: 10.1021/pr900795g
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiling of Rat Brain and Cognitive Behavioral Tasks: Potential Complementary Strategies in Preclinical Cognition Enhancement Research

Abstract: In this study, the correlation between the metabolic profiles of rats undergoing cognition enhancement drug therapy and their associated cognitive behavioral outcomes were investigated. Male Lister Hooded rats were administered either with donepezil, galantamine, or vehicle and subjected to Atlantis watermaze training and novel object recognition tests. An UPLC/MS/MS method was developed to profile 21 neurologically related metabolites in the rat brains. Pharmacologically induced behavioral changes were compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Whole brain was used to obtain a broad picture of whether brain chemistry was altered, which has been useful in initial studies 40,41 . This allowed us to examine the overall macro-physiological changes in brain lipids and polar metabolites in response to stress and whether these differ broadly between rat strains.…”
Section: Discussionmentioning
confidence: 99%
“…Whole brain was used to obtain a broad picture of whether brain chemistry was altered, which has been useful in initial studies 40,41 . This allowed us to examine the overall macro-physiological changes in brain lipids and polar metabolites in response to stress and whether these differ broadly between rat strains.…”
Section: Discussionmentioning
confidence: 99%
“…and the Science Research sampling time and gender differences [190] Mercapturic acids human urine LC-NLS PCA, PLS-DA, OSC negative control vs acetaminophentreated group [186] Neurotransmitter metabolites rat brain UPLC-MRM PCA, OPLS-DA, ROC, PLS-DA vehicle-dosed vs drug-dosed rats [191] Endo-metabolites human plasma LC-MRM PCA normal vs liver failure patient [192] Hydrophilic metabolites in mouse tissues mouse urine, liver, duodenum, kidney, plasma, heart, skeletal muscle…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Specifically, a lot of laboratory studies have shown that the object recognition task in rodents is highly sensitive to psychoactive drug. For example, this is the case of drugs such as acetylcholinesterase inhibitors (AChEIs) which can improve object memory performance in rats [Prickaerts et al, 2002;Hornick et al, 2008;Goh et al, 2009]. In fact, in rats these ACh enhancers can reverse drug-induced memory impairments [Bejar et al, 1999;van der Staay and Bouger, 2005;Yamada et al, 2005].…”
Section: The Object Recognition Testmentioning
confidence: 99%